2016
DOI: 10.23849/npafcb6/61.72
|View full text |Cite
|
Sign up to set email alerts
|

Early Marine Migration of Juvenile Chum Salmon Along the Pacific Coast of Eastern Hokkaido

Abstract: This book that contains 38 research articles on marine ecology of Pacific salmon and steelhead trout, is dedicated to the International Year of the Salmon and is the first scientific publication that contributes to the library of the project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…The species detected in this study add more information to the findings of previous reports on zooplankton (Asami et al, 2007; Hikichi et al, 2018; Hirai et al, 2015, 2017; Pinchuk & Paul, 2000), harmful algal species (Sildever et al, 2019; Stonik & Orlova, 2013), winter microalgal communities (Yan et al, 2022), and protists in general (Matsumoto et al, 2021). Using zooplankton as an example, similar to previous studies from the same sampling location, most of the OTUs were associated with copepods (especially calanoids), Polychaeta, and Hydrozoa (Hirai et al, 2015, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…The species detected in this study add more information to the findings of previous reports on zooplankton (Asami et al, 2007; Hikichi et al, 2018; Hirai et al, 2015, 2017; Pinchuk & Paul, 2000), harmful algal species (Sildever et al, 2019; Stonik & Orlova, 2013), winter microalgal communities (Yan et al, 2022), and protists in general (Matsumoto et al, 2021). Using zooplankton as an example, similar to previous studies from the same sampling location, most of the OTUs were associated with copepods (especially calanoids), Polychaeta, and Hydrozoa (Hirai et al, 2015, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…8), there were great annual variations in both indices. Additional regional surveys in the Kushiro coast in the eastern region of the Pacifi c Ocean also showed that the distribution of juvenile chum salmon was related to coastal seawater temperature aff ected by the cold Coastal Oyashio Current (Kasugai et al 2016). In contrast, western regions showed no signifi cant correlations, although negative correlations were found in the mid-and southern regions of the Japan Sea (Fig.…”
Section: Results Of Coastal Surveymentioning
confidence: 91%
“…Water temperature also affects the temporal and spatial distributions of predatory fishes and juvenile salmon in coastal waters, which may be linked to salmon mortality (Emmett et al, 2006) and migration (Bøe et al, 2019; Byron & Burke, 2014). In coastal waters off Abashiri and Kushiro, eastern Hokkaido, juvenile chum salmon residing within 1 km of shore commence their offshore migration when SST exceeds 8°C (Kasugai et al, 2016; Nagata et al, 2007). The potential effects of sea temperature on salmon survival are so many and varied, and they probably work in conjunction with other factors such as metabolism, food supply, and predator encounters.…”
Section: Discussionmentioning
confidence: 99%